Affective attention under cognitive load: reduced emotional biases but emergent anxiety-related costs to inhibitory control - Berggren, Nick; Richards, Anne; Taylor, Joseph; Derakshan, Nazanin (Frontiers in Human Neuroscience, 2013)
Trait anxiety is associated with deficits in attentional control, particularly in the ability to inhibit prepotent responses. Here, we investigated this effect while varying the level of cognitive load in a modified antisaccade task that employed emotional facial expressions (neutral, happy, and angry) as targets. Load was manipulated using a secondary auditory task requiring recognition of tones (low load), or recognition of specific tone pitch (high load). Results showed that load increased antisaccade latencies on trials where gaze towards face stimuli should be inhibited. This effect was exacerbated for high anxious individuals. Emotional expression also modulated task performance on antisaccade trials for both high and low anxious participants under low cognitive load, but did not influence performance under high load. Collectively, results a) suggest that individuals reporting high levels of anxiety are particularly vulnerable to the effects of cognitive load on inhibition, and b) support recent evidence that loading cognitive processes can reduce emotional influences on attention and cognition.